1998
DOI: 10.1111/j.1749-6632.1998.tb10710.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Expression of Galanin and Galanin Receptors in Dorsal Root Ganglia and Spinal Cord after Axotomy and Inflammation a

Abstract: Galanin can normally be detected only in a few dorsal root ganglion (DRG) neurons, but it is dramatically upregulated after peripheral nerve injury in both rat and monkey. Galanin is stored in large dense core vesicles, which after axotomy are often found close to the membrane of afferent nerve endings in the dorsal horn. In the monkey there is an increase in galanin in many nerve terminals in the superficial dorsal horn after axotomy, but such an increase is more difficult to detect in the rat. Galanin is als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
83
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 45 publications
(65 reference statements)
6
83
1
Order By: Relevance
“…Several studies have demonstrated changes in GALR1 expression acutely after lesions that lead to altered expression levels of galanin Zhang et al, 1998). Often, changes in the expression of galanin mRNA and GALR1 mRNA are inversely related; for example as a A 35 S-labeled riboprobe corresponding to the entire coding region of preprogalanin was applied to 20-m fresh-frozen sections, which were dipped in photographic emulsion, and exposed for 7 days.…”
Section: Regulation Of Galr1 Expression In Galtg Micementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated changes in GALR1 expression acutely after lesions that lead to altered expression levels of galanin Zhang et al, 1998). Often, changes in the expression of galanin mRNA and GALR1 mRNA are inversely related; for example as a A 35 S-labeled riboprobe corresponding to the entire coding region of preprogalanin was applied to 20-m fresh-frozen sections, which were dipped in photographic emulsion, and exposed for 7 days.…”
Section: Regulation Of Galr1 Expression In Galtg Micementioning
confidence: 99%
“…Based on studies involving a GALR2 specific agonist, Lui et al have suggested that GALR1 activation subserves galanin's antinociceptive effects, whereas activation of GALR2 may actually decrease pain threshold (Liu et al, 2001). Also, GALR1 and GALR2 are oppositely regulated following manipulations that alter levels of galanin mRNA, implying distinct physiological roles for each receptor subtype (Burazin et al, 2001;Zhang et al, 1998). Conclusive evidence for alterations in neuropeptide receptor mRNA as a function of ligand overexpression is scant.…”
Section: Regulation Of Galr1 Expression In Galko Micementioning
confidence: 99%
“…Zhang et al, 1995;Xu et al, 1997). Importantly, the expression of both these neuropeptides and their receptors are strongly altered after peripheral nerve injury and/or inflammation (Ji et al, 1994(Ji et al, , 1995X. Zhang et al, , 1998Xiao et al, 2002), suggesting their potential roles in modulating pathological pain.…”
Section: Introductionmentioning
confidence: 97%
“…Somatostatin and its receptors are expressed in a subset of small DRG neurons and activation of peripheral somatostatin receptors reduces inflammatory nociceptive behavior (Hökfelt et al, 1976;Carlton et al, 2001;Bar et al, 2004). Moreover, low levels of galanin, neurotensin, and neuropeptide Y are expressed in DRG neurons under normal circumstance, in addition to their expression in the spinal dorsal horn neurons (Todd et al, 1994;Simmons et al, 1995;X. Zhang et al, , 1998Polgar et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, beyond the diversity of their signaling mechanisms and distributions, we understand relatively little about the physiological role played by any of the different galanin receptor subtypes. This is partly attributable to the fact there are few (if any) receptorspecific ligands available (2, 31, 43, 57), and to date, only one of the receptors (GALR1) has been genetically targeted for ablation for the purpose of studying the resultant phenotype (4,18,23,26,34,56).GALR2 has been implicated in the mediation of galanin's effect on jejunal contraction (54), stimulation of growth hormone and prolactin secretion (11,40), myometrial contraction (38), seizure susceptibility (34), peripheral nerve regeneration (8, 32), hippocampal neuroprotection (12, 33), and the response to axotomy in motor and sensory neurons (48,58). In the case of GALR2, its mRNA has been localized to hypothalamic nuclei, hippocampus, amygdala, several regions of the cortex, and the dorsal root ganglion (reviewed in references 11, 20, 29, and 39) and has been shown to be regulated following peripheral nerve axotomy (48,58).…”
mentioning
confidence: 99%